Empirical and numerical determination of the freezing point depression of an unsteady flow in a scraped surface crystallizer. (October 2020) - Acosta, Carlos A.; Bhalla, Amar; Guo, Ruyan
Highlights: Continuous agitation contributes in the freezing point of aqueous solutions. Phase-transition is captured between 500–600 nm and 700–800 nm. Relationship between absorbance and temperature is inversely proportional. Abstract: Scraped surface Crystallizers are widely used in the chemical and food industry to homogenize viscous fluids during a material phase transition through nucleation by removing heat while continuously mixing with an agitator. Obtaining in-situ measurements using particle velocimetry/thermometry techniques is a challenging task due to the inaccessibility to the interrogation region given the rotating components and the cooling jacket attached to the mixing chamber. Also, fluid dynamics simulations offer quantitative information about the microscopic mass and heat transfer characteristics, but they are difficult to validate given the absence of symmetry, lack of experimental data, and weak characterization of the physical system. The goal of this research was to determine the freezing temperature of a multi-phase aqueous solution using optical absorbance in-situ. Results show significant variations in optical signatures at the phase-transition temperature in the ultra-violet and visible spectrum. A numerical simulation was developed to characterize the fluid dynamics and temperature gradients. Measurements of pressure and temperature validated the predicted values from the transient computational model.